Pistol Whipped - Roel Reine; Henriksen, Lance; Samantha Ryan Maisano; Renee Goldsberry; Lydia Jordan; Fernando Chien (Sony Pictures USA, 2008)
The only man who has Matt's back is married to his ex-wife and has legal custody of his daughter. Even worse Matt's heavy drinking and excessive gambling continually ruin his attempts to be a decent father. Matt gets a chance at a fresh start when a mysterious old man buys up all of his outstanding gambling debts. However in return he must pledge his absolute loyalty and use his talents to kill the city's most notorious criminals. Matt must learn the politics of the underworld and grapple with his role as hired muscle. He soon realizes that there is more going on than meets the eye. As the pressures of his new world come crashing down around him he finally finds the redemption he's been searching for.
Languages: English, French, Czech, Hungarian, Polish Subtitles: English, French, Arabic, Bulgarian, Serbo-Croatian, Czech, Danish, Dutch, Estonian, Finnish, Greek, Hebrew, Hindi, Hungarian, Icelandic, Norwegian, Polish, Romanian, Slovenian, Slovak, Swedish, Turkish
Keywords: Action; Adventure